Recombinant human arginase induces apoptosis through oxidative stress and cell cycle arrest in small cell lung cancer. Issue 11 (6th October 2018) - Xu, Shi; Lam, Sze‐Kwan; Cheng, Paul Ning‐Man; Ho, James Chung‐Man
Abstract : Small cell lung cancer (SCLC) accounts for approximately 13% of all lung cancer cases. Small cell lung cancer is characterized by frequent relapse, and current treatments lack tumor specificity. Arginine is a non‐essential amino acid for human normal cells but critical to some tumor cells that cannot synthesize arginine. Therefore, arginine deprivation has become a potential therapeutic option for selected tumors. BCT‐100 is a pegylated arginase that has documented anticancer activity in arginine auxotrophic tumors, such as melanoma, hepatocellular carcinoma, and acute myeloid leukemia. One of the resistance mechanisms to arginase treatment is overexpression of argininosuccinate synthetase (ASS1) and ornithine transcarbamylase (OTC), two important enzymes in the urea cycle. We selected 9 SCLC and 1 non‐small cell lung carcinoma cell lines to determine the growth inhibition effects of BCT‐100 and established that cell lines with low expression of ASS1 and OTC are relatively sensitive to BCT‐100 treatment. Knocking down OTC in a H841 cell line could potentiate its sensitivity to BCT‐100 treatment. Arginine concentration was sharply decreased, accompanied by apoptosis through oxidative stress as well as G1 cell cycle arrest. In addition, BCT‐100 showed an anticancer effect on H446 and H510A xenograft models by lowering arginine levels and inducing apoptosis. Abstract : BCT‐100 is one type of pegylated recombinant human arginase. BCT‐100 showed an anticancer effect against small cell lung cancer through oxidative stress, apoptosis, and cell cycle arrest.